The performance and long-term stability of low-cost separators in single-chamber bottle-type microbial fuel cells. Issue 3 (1st February 2018) - Kondaveeti, Sanath; Kakarla, Ramesh; Kim, Hong Suck; Kim, Byung-goon; Min, Booki
ABSTRACT: This study evaluates long-term stability of low-cost separators in single-chamber bottle-type microbial fuel cells with domestic wastewater. Low-cost separators tested in this study were nonwoven fabrics (NWF) of polypropylene (PP80, PP100), textile fabrics of polyphenylene sulfide (PPS), sulfonated polyphenylene sulfide (SPPS), and cellulose esters. NWF PP80 separator generated the highest power density of 280 mW/m 2, which was higher than with ion-exchange membranes (cation exchange membrane; CEM = 271 mW/m 2, cation exchange membrane; CMI = 196 mW/m 2, Nafion = 260 mW/m 2 ). MFC operations with other size-selective separators such as SPPS, PPS, and cellulose esters exhibited power densities of 261, 231, and 250 mW/m 2, respectively. During a 280-day operation, initial power density of PP80 (278 mW/m 2 ) was decreased to 257 mW/m 2, but this decrease was smaller than with others (Nafion: 265–230 mW/m 2 ; PP100: 220–126 mW/m 2 ). The anode potential of around −430 mV did not change much with all separators in the long-term operation, but the initial cathode potential gradually decreased. Fouling analysis suggested that the presence of carbonaceous substance on Nafion and PP80 after 280 days of operation and Nafion was subject to be more biofouling.